AN ANALYSIS OF ENGLISH TEACHER’S COMPETENCES AT SENIOR HIGH SCHOOLS IN PANGKEP - Sri Fausyia; Syarifuddin Dollah; La Sunra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of this study was to determine the competence of English teachers in senior high schools in Pangkep. This study used a qualitative method. The population of this study included teachers in senior high schools in Pangkep, with the sample consisting of English teachers from SMAN 2 Pangkep, SMAN 9 Pangkep, and SMAN 10 Pangkep. The research instrument used was an observation checklist. The results showed that English teachers from the three schools demonstrated good professional, personality, and social competence. However, in terms of pedagogical competence, all three schools, especially SMAN 10 Pangkep, needed improvement. At SMAN 10 Pangkep, pedagogical competence was not well implemented because the learning process still took place online, as students came from the islands in Pangkep, thus hindering the proper implementation of this competence.